Social justice: Interdisciplinary inquiries from India - Cybil K.V. (My University, 2025)
This book explores the political and philosophical underpinnings of exclusion and social injustice in India. It examines social movements, anti-caste uprisings, reformers like Ambedkar and Narayana Guru and writers like Foucault and Serres to establish a link between the political and social milieu of the idea of nationhood. Going beyond the legal framework of justice, the essays in the volume reassemble the social from popular perception and the margins, and challenge Rawlsian and Eurocentric paradigms which have dominated discourse on social injustice. The volume also draws on instances of history as well as contemporary issues, as well as locating them in the context of social and post-colonial theory. An intellectually stimulating yet subaltern engagement with the idea of justice, the volume will be of great interest to scholars and researchers of social theory, law, modern South Asian history and social exclusion and discrimination studies. © 2019 K. V. Cybil. All rights reserved.